Climate change and mental health: position paper of the European Psychiatric Association - Brandt, Lasse; Adorjan, Kristina; Catthoor, Kirsten; Chkonia, Eka; Falkai, Peter; Fiorillo, Andrea; Gondek, Tomasz M.; Vay, Jessica Newberry Le; Rojnic, Martina; Meyer-Lindenberg, Andreas; Heinz, Andreas; Dom, Geert; et al. (European psychiatry, 2024)
BackgroundClimate change is one of the greatest threats to health that societies face and can adversely affect mental health. Given the current lack of a European consensus paper on the interplay between climate change and mental health, we signal a need for a pan-European position paper about this topic, written by stakeholders working in mental health care.MethodsOn behalf of the European Psychiatric Association (EPA), we give recommendations to make mental health care, research, and education more sustainable based on a narrative review of the literature.ResultsExamples of sustainable mental healthcare comprise preventive strategies, interdisciplinary collaborations, evidence-based patient care, addressing social determinants of mental health, maintaining health services during extreme weather events, optimising use of resources, and sustainable facility management. In mental health research, sustainable strategies include investigating the impact of climate change on mental health, promoting research on climate change interventions, strengthening the evidence base for mental health-care recommendations, evaluating the allocation of research funding, and establishing evidence-based definitions and clinical approaches for emerging issues such as ‘eco-distress’. Regarding mental health education, planetary health, which refers to human health and how it is intertwined with ecosystems, may be integrated into educational courses.ConclusionsThe EPA is committed to combat climate change as the latter poses a threat to the future of mental health care. The current EPA position paper on climate change and mental health may be of interest to a diverse readership of stakeholders, including clinicians, researchers, educators, patients, and policymakers.
Gesehen am 16.12.2024